Adipose derived mesenchymal stem cell therapy in the treatment of isolated knee chondral lesions: design of a randomised controlled pilot study comparing arthroscopic microfracture versus arthroscopic microfracture combined with postoperative mesenchymal stem cell injections. Issue 12 (18th December 2015) - Freitag, Julien; Ford, Jon; Bates, Dan; Boyd, Richard; Hahne, Andrew; Wang, Yuanyuan; Cicuttini, Flavia; Huguenin, Leesa; Norsworthy, Cameron; Shah, Kiran
Abstract : Introduction: The management of intra-articular chondral defects in the knee remains a challenge. Inadequate healing in areas of weight bearing leads to impairment in load transmission and these defects predispose to later development of osteoarthritis. Surgical management of full thickness chondral defects include arthroscopic microfracture and when appropriate autologous chondrocyte implantation. This latter method however is technically challenging, and may not offer significant improvement over microfracture. Preclinical and limited clinical trials have indicated the capacity of mesenchymal stem cells to influence chondral repair. The aim of this paper is to describe the methodology of a pilot randomised controlled trial comparing arthroscopic microfracture alone for isolated knee chondral defects versus arthroscopic microfracture combined with postoperative autologous adipose derived mesenchymal stem cell injections. Methods and analysis: A pilot single-centre randomised controlled trial is proposed. 40 participants aged 18–50 years, with isolated femoral condyle chondral defects and awaiting planned arthroscopic microfracture will be randomly allocated to a control group (receiving no additional treatment) or treatment group (receiving postoperative adipose derived mesenchymal stem cell treatment). Primary outcome measures will include MRI assessment of cartilage volume and defects and the Knee Injury and Osteoarthritis Outcome Score. Secondary outcomes will include further MRI assessment of bone marrow lesions, bone area and T2 cartilage mapping, a 0–10 Numerical Pain Rating Scale, a Global Impression of Change score and a treatment satisfaction scale. Adverse events and cointerventions will be recorded. Initial outcome follow-up for publication of results will be at 12 months. Further annual follow-up to assess long-term differences between the two group will occur. Ethics and dissemination: This trial has received prospective ethics approval through the Latrobe University Human Research Ethics Committee. Dissemination of outcome data is planned through both national and international conferences and formal publication in a peer-reviewed journal. Trial registration number: Australia and New Zealand Clinical Trials Register (ANZCTR Trial ID: ACTRN12614000812695).